Subjective well-being of veterinary medicine students in Chile - Weinborn Astudillo, Romy (2025)
Mental health is one of the topics that has become increasingly important in the university community in recent years, especially in Veterinary Medicine, a profession with one of the highest suicide rates. The study aimed to determine the subjective well-being of veterinary medicine students from two higher education institutions in central Chile, considering both experienced and remembered well-being. A quantitative, descriptive, and non-experimental method was used with a non-probability sample (n=97) comprised of students from Santiago (n=46) and Viña del Mar (n=51). They voluntarily completed the Pemberton Happiness Index (PHI) questionnaire. Their remembered well-being was 5.2, and their experienced well-being was 5.1, values considered low. Furthermore, 56% of students report on recent well-being experiences. The results indicate that the surveyed population is likely to experience fewer positive experiences than other populations worldwide. It is noted and emphasized the need to strengthen training processes in the cross-curricular area, specifically emotional competencies, in order to improve students' subjective well-being by influencing their perception of happiness and life satisfaction.